COGNAC consumption: A comparative study on American and Chinese consumers - Lingfang Song; Yujie Wei; Blaise Bergiel (Wine Economics and Policy, 2018)
Being a French traditional prestigious spirit, cognac has a strong export orientation, with a majority of the product being consumed internationally. The United States is the largest market in volume and China the largest in value. This paper aims to study consumer behaviors of the two countries in terms of their preferences, motivations, and consumption patterns towards cognac. By studying 248 valid responses from the United States and 256 valid responses from China, our study reveals significant differences between the two groups. The study allows a better understanding of the markets. It provides useful insights in the development of market potentials, designing marketing communications, and adaptation of product features relating to cognac. It may also stimulate reflections for wine and other spirit companies for their business in the two markets.
Keywords: 330; Cognac; Consumer behaviors; Marketing